2018
DOI: 10.1097/scs.0000000000004415
|View full text |Cite
|
Sign up to set email alerts
|

Successful Strategies for Dealing With Infected, Custom-Made Hydroxyapatite Cranioplasty

Abstract: When a cranioplasty implant becomes infected, standard operating procedure dictates its removal and the initiation of a long course of antibiotic therapy. However, removing such a prosthesis can have a series of adverse consequences, including delayed cognitive and motor recovery, lack of brain tissue protection, unsightly deformity, and the need for two additional surgical procedures, not to mention the additional costs involved. To maintain the advantages of cranioplasty, we opted for a conservative approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…As reported by Zanotti et al, 19 one patient with infection and no exposed hardware postcranioplasty underwent levofloxacin and rifampicin every 24 hours for 8 weeks followed by debridement. At 2-year follow-up, the patient remained infection-free 19 . Johnson et al 22 treated a patient with skin necrosis and exposure of hardware with IV antibiotics for 3 weeks followed by debridement, drainage of infected tissue, scalp rotation flap, and 3 more weeks of antibiotics.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations
“…As reported by Zanotti et al, 19 one patient with infection and no exposed hardware postcranioplasty underwent levofloxacin and rifampicin every 24 hours for 8 weeks followed by debridement. At 2-year follow-up, the patient remained infection-free 19 . Johnson et al 22 treated a patient with skin necrosis and exposure of hardware with IV antibiotics for 3 weeks followed by debridement, drainage of infected tissue, scalp rotation flap, and 3 more weeks of antibiotics.…”
Section: Resultsmentioning
confidence: 82%
“…The authors indicated that they could avoid prosthesis removal due to targeted antibiotic therapy, wound surgical revision, and the biomimetism of HA prosthesis. Zanotti et al 19 successfully salvaged an infected HA cranioplasty prosthesis without explantation through the use of targeted antibiotics followed by debridement. Six years after treatment, the patient revealed no problems or reinfections with the implant 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This method allows to decrease implant-associated infection by decreasing bacterial adherence and subsequent colonization. 49 Local delivery of antibiotics allows to deliver a high, locally effective dose whereas maintaining a low plasma concentration to minimize or eliminate systemic toxicity.…”
Section: Discussionmentioning
confidence: 99%